Impact of applied cell voltage on the performance of a microbial electrolysis cell fully catalysed by microorganisms. (24th January 2020) - Lim, Swee Su; Fontmorin, Jean-Marie; Izadi, Paniz; Wan Daud, Wan Ramli; Scott, Keith; Yu, Eileen Hao
Abstract: The effect of the operating voltage on the performance of a microbial electrolysis cell (MEC) equipped with both a bioanode and a biocathode for hydrogen production is reported. Chronoamperometry tests ranged between 0.3 and 2.0 V were carried out after both bioelectrodes were developed. A maximum current density up to 1.6 A m −2 was recorded at 1.0 V with hydrogen production rate of nearly 6.0 ± 1.5 L m −2 cathode day −1 . Trace amounts of methane, acetone and formate were detected in cathode's headspace and catholyte which followed the same trend as hydrogen production rate. Meanwhile substrate consumption in anolyte also followed the trend of hydrogen production and current density changes. The bioanode could utilise up to 95% of acetate in the tested voltage ranges, however, at a cell voltage of 2.0 V the bioanode's activity stopped due to oxygen evolution from water hydrolysis. Cyclic voltammograms revealed that the bioanode activity was vital to maintain the functionality of the whole system. The biocathode relied on the bioanode to maintain its potential during the hydrogen evolution. The overall energy efficiency recovered from both bioanode and external power in terms of hydrogen production at the cathode was determined as 29.4 ± 9.0%, within which substrate oxidation contributed up to nearly 1/3 of the total energy marking the importance of bioanode recovering energy from wastewater to reduce the external power supply. Highlights: Bioelectrodes in the MEC were enriched simultaneously and stable operated over a year. The highest hydrogen production (5.9 L H2 /m 2 cathode/day) occurred at 1.0 V. PH divergence was inevitable between the chambers and at its maximum after ≥1.0 V. High applied voltage (>1.2 V) had adverse effect against bioanode. Overall energy efficiency was 29.4% and bioanode provided almost 1/3 of the total energy.